Vybrané aspekty sociálních služeb pro seniory - Halásková, Renáta (Univerzita Pardubice, 2012)
The article focuses on issues of social services, which are defined as an instrument of social policy and form of social assistance for the benefit of another person. In the broader context are defined social services as services of general interest (social assistance services, employment services and education, social housing and long-term care). In connection with the specifics of social services attention is paid to the economic characteristics of social services, demographic aspects and ageing of population and the importance of social services for the elderly. Based on the survey assessment of satisfaction, which is one of the indicators quality assessment of social services, are to documented results of survey satisfaction of the elderly with the services in selected residential facilities and satisfaction of the elderly with services by type of provider.
Selected aspects of social services for the elderly
Keywords: social services; social services of general interest; residential social services; demographic ageing; elderly; assessment of safisfaction